STRATEGI KOPING OLEH EUMAH TANGGA MISKIN DI KABUPATEN CIREBON - Suparman Suparman; Pusparini Pusparini; Mimin Aminah; Hardinsyah Hardinsyah; Ikeu Tanziha (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2008)
Coping Strategy Among Poor Households In Cirebon District.Background: Decision of every household to minimize the effect of food insecurity depend on its capacity to give appropriate response. Poor coping strategy create adverse effect to the households.Objectives: To learn how poor households apply a coping strategy and their related factors when they met insecure situation.Methods: A cross-sectional study was conducted in three villages in Cirebon District, each representing of high, medium, and low in food security village based on macro-sector data. From each village 21 poor househqlds wereselected randomly. There are six variables collected consist of mother education, number of household, number ofchildren under five years, occupation of head of household, perception about food insecurity, how often implementedparticular coping strategies, household expenditure and child nutritional status.Results: Prevalence under weight (weight for age) was 50.8% and assosiated with to a type of coping strategy on the reducing of food supply in the household (rs: - 0.255). There were also association between household expenditure and several parameters of coping strategy (income gathering and other parameters related to reducing food intake). The more frequent the hosuehold reducing the amount of food items for consumption, the higher the proportion of undernourished children.Conclusions: Reducing daily food supply as a simple modified to cope food insecurity conducted by households higly correlated to poor nutritional status of under-five years old children. Appropriate coping strategy should be developed by local government and disseminate properly to poor households on anticipating insecurity situation.Keywords: food security, poor households, coping strategies, nutritional status